2014
DOI: 10.1016/j.jss.2013.11.493
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Radiotherapy is Associated with Improved Survival among Patients with Synovial Sarcoma: A SEER Analysis

Abstract: Background and Methods-We examined the outcomes of synovial sarcoma (SS) patients in a national database. We identified 1,189 patients from the Surveillance, Epidemiology, and End Results (SEER) database with data on site and extent of surgery. We excluded patients diagnosed before 1990, <18 years, or lacking pathologic confirmation. Using Kaplan-Meier and Cox proportional hazards analyses, we determined predictors of overall (OS) and disease-specific survival (DSS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…(Neo)adjuvant radiation may be administered depending on the specific clinical situation. Retrospective studies have reported that radiotherapy has a positive effect on event-free survival [4], local recurrence-free survival [27], and disease-specific survival as well as OS [28].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…(Neo)adjuvant radiation may be administered depending on the specific clinical situation. Retrospective studies have reported that radiotherapy has a positive effect on event-free survival [4], local recurrence-free survival [27], and disease-specific survival as well as OS [28].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Egy másik vizsgálat szerint az adjuváns RT növeli az 5 éves LRFS-t (80%) és PFS-t (52%) [19]. A SEER-adatbázis szerint a perioperatív RT túlélési előnyt jelent SS-ben [20]. Egy 29 éves periódust tekintve a makroszkópos reszekciót követő adjuváns KT után nőtt az 5 éves MFS (47% vs. 27%) a 17. életévet betöltött betegek körében (n = 215) [21].…”
Section: Kezelés éS Kimenetelunclassified
“…Az NCT02181829 klinikai vizsgálat a teljes tüdő intenzitásmodulált radioterápia hatását határozza meg. Palliatív kemoterápiával 42-46%-os parciális remiszszió érhető el (n = 12) [20]. A salvage kemoterápiás sé-mák között sem válaszarányban, sem túlélésben nincs különbség [27].…”
Section: Kezelés éS Kimenetelunclassified